A cycle-jump acceleration method for the crystal plasticity simulation of high cycle fatigue of the metallic microstructure. (December 2022) - Cheng, Jiahao; Hu, Xiaohua; Kirka, Michael
Highlights: A "cycle-jump" acceleration method is developed for microstructure-based high-cycle crystal plasticity finite element simulation. The acceleration is based on periodic backward Eulerian extrapolation of internal variables and stress re-equilibration, with adaptive acceleration control. The model has been tested under various cyclic loading conditions, including different load magnitudes, R ratio, strain/load control modes.. The model has been implemented for both Voce hardening law and dislocation density-based hardening law, showing good accuracy and efficiency. Abstract: For metallic materials, high-cycle fatigue life is sensitive to underlying microstructure features including secondary phases, textures, grains morphology, etc. The traditional, data-based safe-life approaches for modeling fatigue don't explicitly consider the microstructure and can't guide study in microstructure modification for improved fatigue property. Crystal plasticity-based simulation provides increased model fidelity at the expense of immense computation time, making it inapplicable for high cycle fatigue. In this work, an acceleration method based on cycle-jump approach (Lesne and Savalle, 1989) was developed for microstructure-based high-cycle FE simulation using crystal plasticity constitutive-model. This method demonstrated high efficiency in benchmark tests of various conditions.